Investigating the Typology of Causative Constructions in the Semnani Language - Ebrahim Rezapour; Mona Pishgoo (مطالعات زبانی و بلاغی)
The present study investigated the typology of causative constructions in the Semnani language. The language of Semnani is one of the live languages in Iran that is endangered to gradual extinction. Therefore, the speakers of this language must study and record it to save it and prevent its extinction. Investigating the causative constructions of Semnani language, the present research tries to study the typology of causative constructions in this Language and to find the similarities and differences between Persian and Semnani causative constructions. Using the questionnaire and interviews from ten Semnani speakers and the descriptive-analytic method, the researcher investigated Semnani causative constructions by the typology method of causative constructions. The research results indicate the existence of compound causative constructions and simple ones including equal, unequal, and compound unequal lexical causatives, morphological causatives (first, second and third types), and auxiliary causatives in the Semnani language.